2016
DOI: 10.1097/md.0000000000002395
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin for Risk Stratification of Emergency Patients With Nonspecific Complaints

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…45 In a very recent study, they suggested an algorithm that combined MR-proADM levels with clinical assessment to detect patients who could be discharged from hospital early and with acceptable safety. 14 Nickel and colleagues presented MR-proADM decisive cutoffs between 0.75 nmol/L and 1.5 nmol/L that are comparable to our calculated preoperative MR-proADM cutoff for AKI. We showed that MR-proADM change was a better risk estimator than a single value.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…45 In a very recent study, they suggested an algorithm that combined MR-proADM levels with clinical assessment to detect patients who could be discharged from hospital early and with acceptable safety. 14 Nickel and colleagues presented MR-proADM decisive cutoffs between 0.75 nmol/L and 1.5 nmol/L that are comparable to our calculated preoperative MR-proADM cutoff for AKI. We showed that MR-proADM change was a better risk estimator than a single value.…”
Section: Discussionsupporting
confidence: 80%
“…Among the newly emerging biomarkers, adrenomedullin (ADM) is viewed as one of the candidates that may guide diagnostic and therapeutic decision-making. 13,14 Adrenomedullin belongs to the calcitonin gene-related peptide family and, besides multiple endocrine biological processes, triggers a distinct vasodilation of resistance vessels. 15,16 Adrenomedullin interacts with several complex physiological pathways such as immunomodulation, diuretic, and bactericidal effects.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale to focus on these patients is the lack of a standardized work-up, the high use of resources, and the risk of adverse outcomes [5][6][7][8]. All publications originating from the prospective multicenter Basel Nonspecific Complaints (BANC) cohorts used the above definition of NSCs [9][10][11][12], but other studies have used varying criteria to define NSCs [13]. There is an inherent difference regarding inclusion criteria between the studies considered by the present systematic review, e.g., some of the included studies were retrospective, and one study [14] has used a post-hoc classification of nonspecific complaints [15].…”
Section: Dear Editormentioning
confidence: 99%
“…Stratification of patients with lower respiratory infection based on a clinical algorithm including ProADM stratification tended to shorten length of hospital stay without an increase in adverse clinical outcome [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%